Nickel metal battery electrolyte, preparation method and application
By using an electrolyte composed of nickel salt and organic solvent, the problems of low voltage windows and side reactions in aqueous nickel metal batteries are solved, and efficient deposition/peeling and stability of nickel metal batteries in the three-electrode system are achieved, simplifying the preparation process and reducing costs.
Patent Information
- Application Number
- CN202510707325.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-08-29
AI Technical Summary
The problems of low voltage windows and side reactions in existing water-based nickel metal batteries have hindered their commercial application.
An electrolyte composed of nickel salt and organic solvent is used to replace the traditional aqueous electrolyte to form a stable solvation structure, inhibit side reactions and broaden the electrochemical window.
The highly reversible deposition/peel of nickel metal batteries in the three-electrode system is achieved, which improves battery performance and stability, reduces by-product generation, simplifies the preparation process and reduces costs.
Smart Images

Figure CN120565848A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nickel metal battery electrolyte, and in particular to a nickel metal battery electrolyte, a preparation method and application thereof. Background Art
[0002] With increasing energy consumption and greenhouse gas emissions, environmental degradation is becoming increasingly severe. The search for alternative clean energy sources has become a global research focus, and the development of safe, environmentally friendly, and cost-effective energy storage technologies is urgent. Rechargeable batteries meet the demand for large-scale energy storage while bringing significant convenience to our lives. However, lithium-ion batteries, currently the primary choice for energy storage, face numerous limitations in their comprehensive application due to limited global lithium resources, the negative environmental impact of their production, and potential safety hazards during operation.
[0003] Compared with the currently widely used lithium-ion batteries, sodium-ion batteries and potassium-ion batteries, aqueous rechargeable batteries have become a highly promising alternative due to their higher safety. High-capacity rechargeable aqueous battery technology plays a key role in the comprehensive utilization of large-scale sustainable and intermittent energy, and has significant advantages in meeting the requirements of advanced facilities such as grid energy storage and electrified transportation for higher availability, efficiency and safety. Aqueous electrolytes have the advantages of low cost, high safety, easy manufacturing and high ionic conductivity. Among aqueous rechargeable batteries, metal batteries that directly use metals as negative electrodes are generally competitive in terms of energy density because metal negative electrodes can provide higher specific capacity than their compound counterparts. However, problems such as dendrite growth and hydrogen evolution reaction at metal negative electrodes have seriously hindered the commercialization of aqueous metal batteries.
[0004] Among the various metal anode carriers, transition metal nickel has a high reaction potential (-0.25 V relative to the standard hydrogen electrode (SHE)), high volumetric capacity (8136 mAh cm -3 ), and up to 913mAh g -1 The weight-to-capacity ratio makes it an extremely advantageous metal negative electrode material. In addition, nickel also has the characteristic of being dendrite-free. However, most of the current related research uses water as the main solvent for the electrolyte. There are serious side reactions in the aqueous electrolyte, such as the formation of a Ni(OH)2 passivation layer. In addition, there is a lot of free water in the aqueous electrolyte, which will decompose and cause hydrogen evolution corrosion at 1.23V (vs. SHE). As a solvent, water has a low electrochemical window. Therefore, there is an urgent need to develop an electrolyte system that suppresses side reactions and has a wider electrochemical window. Summary of the Invention
[0005] The purpose of the present invention is to provide a nickel metal battery electrolyte, preparation method and application, to solve the problems of low voltage window and side reaction generation of aqueous electrolytes, so as to achieve highly reversible metal nickel deposition / stripping in a three-electrode system.
[0006] To achieve the above object, the present invention provides a nickel metal battery electrolyte, which includes a nickel salt and an organic solvent, and the nickel salt concentration is 0.5 to 3 mol / L.
[0007] Preferably, the nickel salt is one of nickel chloride hexahydrate, nickel sulfate hexahydrate, nickel nitrate hexahydrate, and nickel acetate tetrahydrate.
[0008] Preferably, the organic solvent is one of an alcohol solvent, an ester solvent, an ether solvent, and a sulfoxide solvent.
[0009] Preferably, the alcohol solvent is one of methanol, ethanol, ethylene glycol and glycerol.
[0010] Preferably, the ester solvent is one of ethylene carbonate, propylene carbonate, dimethyl carbonate and ethyl methyl carbonate.
[0011] Preferably, the ether solvent is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0012] Preferably, the sulfoxide solvent is dimethyl sulfoxide or dodecyl methyl sulfoxide.
[0013] On the other hand, the present invention provides a method for preparing the above-mentioned nickel metal battery electrolyte, comprising: dissolving nickel salt in a solvent at a nickel salt concentration of 0.5 to 3 mol / L, and stirring thoroughly at room temperature until the nickel salt is completely dissolved to obtain a nickel metal battery electrolyte.
[0014] On the other hand, the present invention provides an application of the above-mentioned nickel metal battery electrolyte in constructing a three-electrode battery, wherein the three-electrode battery uses a surface-modified carbon cloth as a working electrode, a platinum sheet as a counter electrode, and Ag / AgCl as a reference electrode; the working electrode, counter electrode, and reference electrode are placed in a container containing the nickel metal battery electrolyte to assemble the three-electrode battery.
[0015] Preferably, the preparation method of the surface modified carbon cloth comprises: preparing a carbon cloth having a thickness of 310 μm and an area of 1×1 cm 2 The carbon cloth was ultrasonically treated with acetone, water and ethanol for 30 min in sequence, then dried in an oven at 60 °C for 12 h, and finally placed in a plasma cleaner for 6 min.
[0016] Therefore, the nickel metal battery electrolyte, preparation method and application of the present invention have the following beneficial effects:
[0017] (1) The electrolyte of the present invention is composed of a nickel salt and an organic solvent. In a conventional aqueous electrolyte system, water molecules react with nickel ions, prompting the formation of Ni(OH)2 byproducts. These byproducts not only reduce the utilization rate of the active material but also affect the uniformity of the nickel metal deposition. The electrolyte of the present invention uses an organic solvent instead of water, fundamentally eliminating the conditions for the side reaction between water molecules and nickel ions.
[0018] (2) The solvation structure formed by the organic solvent and the nickel salt can form a stable electric field distribution on the electrode surface, so that during the reduction deposition process, nickel ions can obtain electrons and deposit more evenly on the electrode surface under the synergistic effect of the electric field force and the solvation structure, providing a strong guarantee for improving the performance of nickel metal batteries.
[0019] (3) Organic solvents have good solubility and can fully combine with nickel salts to form a uniform and stable system. The special molecular structure of organic solvents can ensure the free movement of ions in the solution without increasing excessive internal friction. On the one hand, there is a moderate interaction between the molecules of the organic solvent and the ions dissociated from the nickel salt. This interaction can not only help the ions disperse, but also not overly constrain the ions, so that the ions can migrate efficiently under the action of the electric field, thereby giving the electrolyte high ionic conductivity. On the other hand, due to the intermolecular force of the organic solvent and the synergistic effect with the nickel salt ions, the cohesive force of the system can be regulated, so that the electrolyte has an appropriate viscosity, which will not cause difficulty in ion migration due to excessively high viscosity, nor will it cause instability in ion dispersion due to too low viscosity.
[0020] (4) The preparation process of the electrolyte of the present invention only involves a simple mixing step and does not require complex equipment and processes, so the preparation method is simple and low-cost; and the raw materials and reaction processes used do not involve the production and emission of toxic and harmful substances, and are safe and environmentally friendly during preparation and use.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0023] Figure 1 The three-electrode battery assembled using the electrolytes of Example 1 and the comparative example was tested at a scan rate of 1 mV·s at 25°C. -1 The LSV comparison chart below;
[0024] Figure 2 The three-electrode battery assembled using the electrolytes of Example 1 and the comparative example was tested at a scan rate of 1 mV·s at 25°C. -1 The CV comparison diagram of the 1st, 2nd, 5th and 10th cycles is shown below; a is the CV of the electrolyte of Example 1 at 1mV·s -1 CV curves of different cycles at different scan rates, b is the CV curve of the comparative electrolyte at 1 mV·s -1 CV curves of different numbers of cycles at sweep speed;
[0025] Figure 3 The three-electrode battery assembled using the electrolytes of Example 1 and the comparative example was tested at a current density of 10 mA·cm at 25°C. -2 , the deposition capacity is 0.5 mAh·cm -2 Comparison of long cycle performance under different conditions;
[0026] Figure 4 The Tafel curves of the three-electrode battery assembled using the electrolytes of Example 1 and the comparative example tested at 25°C;
[0027] Figure 5 Figure a is the capacity-voltage curve of a three-electrode battery assembled using the electrolyte of Example 1 at 25°C, and Figure b is the XRD pattern of deposited and stripped nickel metals with different capacities corresponding to the capacity-voltage curve;
[0028] Figure 6 The three-electrode battery assembled using the electrolytes of Example 1 and the comparative example was tested at a current density of 10 mA·cm at 25°C. -2 , the deposition capacity is 0.5 mAh·cm -2 SEM images under different conditions, where a is the 0.5 mAh·cm deposited on the carbon cloth surface in the electrolyte of Example 1. -2 Scanning electron microscope image of nickel metal, b is 0.5 mAh·cm deposited on the carbon cloth surface in Example 1 -2 SEM image of nickel after stripping. (c) is a comparative example of the electrolytic solution deposited with 0.5 mAh cm on the carbon cloth surface. -2 Scanning electron microscope image of nickel metal, d is the 0.5 mAh·cm deposited on the carbon cloth surface in the comparative example -2 Scanning electron microscope image of nickel after stripping. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below with reference to the accompanying drawings and embodiments.
[0030] In order to make the purpose, technical solutions and advantages of the present application clearer, more thorough and more complete, the technical solutions of the present invention are clearly and completely described below through the accompanying drawings and Examples. The following detailed description is an explanation of the embodiments and is intended to provide further details of the present invention. Unless otherwise specified, all technical terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the application belongs.
[0031] The instruments, equipment, reagents and materials used in the examples were obtained from commercial sources.
[0032] Example 1
[0033] A nickel metal battery electrolyte is disclosed. The nickel salt used is nickel chloride hexahydrate, the concentration of nickel chloride hexahydrate in the electrolyte is 2 mol / L, and the organic solvent is ethylene glycol. The electrolyte A is obtained by fully stirring at room temperature until the nickel salt is completely dissolved.
[0034] Example 2
[0035] A nickel metal battery electrolyte, wherein the nickel salt used is nickel sulfate hexahydrate, the concentration of nickel sulfate hexahydrate in the electrolyte is 2 mol / L, and the organic solvent is ethylene glycol. The electrolyte B is obtained by fully stirring at room temperature until the nickel salt is completely dissolved.
[0036] Example 3
[0037] A nickel metal battery electrolyte is disclosed, wherein the nickel salt used is nickel chloride hexahydrate, the concentration of nickel sulfate hexahydrate in the electrolyte is 2 mol / L, and the organic solvent is glycerol. The electrolyte C is obtained by fully stirring at room temperature until the nickel salt is completely dissolved.
[0038] Example 4
[0039] A nickel metal battery electrolyte is provided, wherein the nickel salt used is nickel chloride hexahydrate, the concentration of nickel sulfate hexahydrate in the electrolyte is 0.5 mol / L, and the organic solvent is dimethyl sulfoxide. The electrolyte D is obtained by fully stirring at room temperature until the nickel salt is completely dissolved.
[0040] Comparative Example
[0041] A conventional aqueous electrolyte is prepared. The nickel salt used is nickel chloride hexahydrate, the concentration of nickel chloride hexahydrate in the electrolyte is 2 mol / L, and the solvent is water, thereby obtaining a nickel chloride aqueous solution electrolyte.
[0042] Test Example 1
[0043] A three-electrode battery was assembled using the electrolytes prepared in Examples 1 to 4 and the comparative example: the treated carbon cloth was used as the working electrode, the platinum sheet was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode. 30 mL of electrolyte was placed in a beaker, and the three electrodes were immersed in the electrolyte in the beaker. The electrochemical performance of the battery was tested on a blue electric test system and an electrochemical workstation.
[0044] The processing technology of carbon cloth is as follows: the thickness of carbon cloth is 310μm and the area is 1×1cm 2 The carbon cloth was ultrasonically treated with acetone, water, and ethanol for 30 min in sequence, then dried in an oven at 60 °C for 12 h, and finally placed in a plasma cleaner for 6 min.
[0045] like Figure 1 As shown, the three-electrode battery assembled using the electrolytes of Example 1 and the comparative example was tested at 25°C with a scan rate of 1 mV·s -1 The linear sweep voltammetry comparison diagram under . It can be seen from the figure that the electrolyte of Example 1 has a wider voltage window than that of the comparative example. -2 The corresponding voltage at the current density is taken as the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) potential of the electrolyte. It can be seen that the electrolyte in Example 1 has a lower HER potential and a higher OER potential.
[0046] Figure 2 The three-electrode battery assembled using the electrolytes of Example 1 and the comparative example has a voltage window of -0.8 to 0.6 V at 25°C and a scan rate of 1 mV s -1 The cyclic voltammetry curves of the 1st, 2nd, 5th and 10th cycles are compared. Wherein, a is the electrolyte of Example 1 at 1mV·s -1 CV curves of different cycles at different scan rates, b is the CV curve of the comparative electrolyte at 1 mV·s -1 CV curves for different numbers of cycles at different scan rates. As can be seen from the figure, the CV curves of the electrolyte in Example 1 almost completely overlap during the 2nd, 5th, and 10th cycles, except during the first activation cycle. However, the CV curves of the comparative electrolyte have a lower overlap, indicating that the electrolyte in Example 1 has excellent deposition / stripping reversibility.
[0047] Figure 3 The three-electrode battery assembled using the electrolytes of Example 1 and the comparative example was tested at a current density of 10 mA·cm at 25°C. -2 , the deposition capacity is 0.5 mAh·cm -2 Long cycle diagram under different conditions. As can be seen from the figure, the comparative example battery fails after 7400 cycles, while the battery of Example 1 can be cycled for more than 100,000 times with an average coulombic efficiency of more than 99.0%, indicating that the battery of Example 1 has ultra-high cycle stability.
[0048] Figure 4 The Tafel curves of the three-electrode battery assembled using the electrolytes of Example 1 and the comparative example were tested at 25°C. In the figure, the corrosion current in the electrolyte of Example 1 is 0.03 mA·cm -2 , the corrosion voltage is 0.42V, and the corrosion current in the comparative electrolyte is 0.31mA·cm -2 , the corrosion voltage is 0.41 V. In the electrolyte of Example 1, the electrolyte has a higher corrosion voltage and a lower corrosion current, indicating better corrosion resistance.
[0049] Figure 5 The capacity-voltage curve of the three-electrode battery assembled using the electrolyte of Example 1 at 25°C ( Figure 5 a) and the corresponding XRD patterns of deposition and stripping of different capacities of nickel metal ( Figure 5 In (b), it can be seen that as the deposition capacity increases, the diffraction peak of metallic nickel gradually increases, indicating the formation of metallic nickel. Further, as the metallic nickel is stripped, the diffraction peak gradually weakens until it disappears, indicating that the deposition and stripping of metallic nickel is highly reversible.
[0050] Figure 6 The three-electrode battery assembled using the electrolytes of Example 1 and the comparative example was tested at a current density of 10 mA·cm at 25°C. -2 , the deposition capacity is 0.5 mAh·cm -2 Scanning electron microscope image under the conditions. The figure shows that 0.5 mAh·cm -2 After the nickel was deposited, the nickel was evenly distributed on the surface of the carbon cloth. No nickel metal appeared on the surface of the carbon cloth after peeling, indicating excellent reversibility of deposition and peeling. -2 It can be seen that white by-products are generated and unevenly distributed. Metal nickel also appears on the surface of the carbon cloth after peeling, indicating that the deposition and peeling are uneven.
[0051] Therefore, the nickel metal battery electrolyte prepared by the present invention broadens the electrochemical window, stabilizes the nickel metal negative electrode, effectively inhibits the generation of by-products during the reaction process, and achieves uniform nickel deposition; the use of the electrolyte of the present application for the deposition / stripping of metallic nickel in a three-electrode system has extremely high coulombic efficiency.
[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solutions of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A nickel metal battery electrolyte, characterized in that: The electrolyte includes nickel salt and an organic solvent, and the concentration of the nickel salt is 0.5-3 mol / L.
2. The nickel metal battery electrolyte according to claim 1, characterized in that: The nickel salt is one of nickel chloride hexahydrate, nickel sulfate hexahydrate, nickel nitrate hexahydrate, and nickel acetate tetrahydrate.
3. The nickel metal battery electrolyte according to claim 1, wherein: The organic solvent is one of an alcohol solvent, an ester solvent, an ether solvent, and a sulfoxide solvent.
4. The nickel metal battery electrolyte according to claim 3, characterized in that: The alcohol solvent is one of methanol, ethanol, ethylene glycol and glycerol.
5. The nickel metal battery electrolyte according to claim 3, characterized in that: The ester solvent is one of ethylene carbonate, propylene carbonate, dimethyl carbonate and ethyl methyl carbonate.
6. The nickel metal battery electrolyte according to claim 3, characterized in that: The ether solvent is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
7. The nickel metal battery electrolyte according to claim 3, characterized in that: The sulfoxide solvent is dimethyl sulfoxide or dodecyl methyl sulfoxide.
8. A method for preparing a nickel metal battery electrolyte according to any one of claims 1 to 7, characterized in that: include: The nickel salt is dissolved in a solvent at a nickel salt concentration of 0.5 to 3 mol / L, and is fully stirred at room temperature until the nickel salt is completely dissolved to obtain a nickel metal battery electrolyte.
9. Use of the nickel metal battery electrolyte according to any one of claims 1 to 7 in constructing a three-electrode battery, characterized in that: The three-electrode cell uses surface-modified carbon cloth as the working electrode, platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode; The working electrode, the counter electrode, and the reference electrode are placed in a container containing nickel metal battery electrolyte to assemble a three-electrode cell.
10. Use of the nickel metal battery electrolyte according to claim 9 in constructing a three-electrode battery, characterized in that: The preparation method of surface modified carbon cloth comprises: preparing a carbon cloth having a thickness of 310 μm and an area of 1×1 cm 2 The carbon cloth was ultrasonically treated with acetone, water and ethanol for 30 min in sequence, then dried in an oven at 60 °C for 12 h, and finally placed in a plasma cleaner for 6 min.
Citation Information
Patent Citations
Organic nickel ion battery electrolyte and organic nickel ion battery
CN114204137A
Preparation method of magnesium ion battery positive electrode material
CN114368783A
Magnesium battery electrolyte
US20140147754A1